OPTIMALKAN PROFIL DESA PAIT UNTUK PERTUMBUHAN DAN PEMBERDAYAAN MASYARAKAT - Muhammad Aris Ichwanto; Joko Samodra; Heru Wahyu Herwanto; Amir Rofiudin; Ary Agung Wibowo; Luhur Adi Prasetya; Salsabila Thifal Nabil Haq; Rian Syahmulloh Hendranawan; Irva Widiyawati; Khusnul Muttaqiyah; Denny Martin; Suhendri (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2025)
This research analyzes the development of the profile of Pait Village in Kasembon District, Malang Regency, as a sustainable village to improve welfare through local potential. Pait Village has great opportunities in the agriculture and tourism sectors, but limited promotion, and digital literacy are the main obstacles. This research used descriptive qualitative methods with case studies and virtual ethnography, involving village officials, communities, tourism managers, tourists, and digital marketing experts. Village profile development was carried out by making promotional videos, from pre-production to distribution through social media. The results show that village profile videos attract tourists and increase sales of local products. However, challenges remain, such as poor infrastructure and lack of community participation due to low digital literacy. The conclusions emphasize the importance of sustainable promotion strategies, infrastructure improvements, and active community participation.